2014
DOI: 10.1007/s10021-014-9772-6
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Contribution of Riparian Inputs to Organic Carbon Pools in Freshwater Systems

Abstract: A lack of appropriate proxies has traditionally hampered our ability to distinguish riverine organic carbon (OC) sources at the landscape scale. However, the dissection of C4 grasslands by C3-enriched riparian vegetation, and the distinct carbon stable isotope signature (δ13C) of these two photosynthetic pathways, provides a unique setting to assess the relative contribution of riparian and more distant sources to riverine C pools. Here, we compared δ13C signatures of bulk sub-basin vegetation (δ13CVEG) with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 73 publications
(122 reference statements)
4
22
0
Order By: Relevance
“…Although corruption is a legitimate concern in Terai forest management [13], it is an issue of governance and can be minimized through government transparency and accountability [35]. Our study results revealed that other stakeholders are not assured of good governance and accountability issues within the existing SFM mechanisms.…”
Section: Resultsmentioning
confidence: 80%
“…Although corruption is a legitimate concern in Terai forest management [13], it is an issue of governance and can be minimized through government transparency and accountability [35]. Our study results revealed that other stakeholders are not assured of good governance and accountability issues within the existing SFM mechanisms.…”
Section: Resultsmentioning
confidence: 80%
“…Similar seasonal patterns in riverine δ 13 C POC have been reported from other catchments with mixed C3 and C4 vegetation [ Bird et al ., ; Zhang et al ., ; Marwick et al ., ], pointing toward a common driver behind the seasonal delivery of C3 versus C4‐derived C to the river systems within tropical and subtropical latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in central Madagascar, the δ 13 C composition of riverine OC is biased toward riparian C3 plants despite the catchment being dominated by C4 grasslands (Marwick et al, 2014). The isotopic composition of riverine OC and terrestrial plant biomarkers can also change between wet and dry seasons, reflecting different fluvial sourcing or OC mobilization mechanisms during wet and dry flow regimes (Marwick et al, 2014;Ponton et al, 2014). Further, the concentration and relative abundance of terrestrial plant nalcohols and n-alkanoic acids in fluvial suspended sediments fluctuate with seasonal change in discharge from the Congo River, while those of the n-alkanes are more stable (Hemingway et al, 2016).…”
Section: Plant Wax Reworking and Temporal Resolutionmentioning
confidence: 95%
“…The δD composition of n-C28 alkanoic acid in riverine POM reflects the average upstream catchment area at each successive point along an elevation gradient in a tributary network to the Amazon (Ponton et al, 2014). In contrast, in central Madagascar, the δ 13 C composition of riverine OC is biased toward riparian C3 plants despite the catchment being dominated by C4 grasslands (Marwick et al, 2014). The isotopic composition of riverine OC and terrestrial plant biomarkers can also change between wet and dry seasons, reflecting different fluvial sourcing or OC mobilization mechanisms during wet and dry flow regimes (Marwick et al, 2014;Ponton et al, 2014).…”
Section: Plant Wax Reworking and Temporal Resolutionmentioning
confidence: 99%